Toll-like Receptors Signaling Pathways as a Potential Therapeutic Target in Cardiovascular Disease - Parizadeh, Seyed M.; Ghandehari, Maryam; Heydari-majd, Motahareh; Seifi, Sima; Mardani, Ramin; Parizadeh, Seyed Mohamadreza; Ghayour-Mobarhan, Majid; Ferns, Gordon A.; Hassanian, Seyed Mahdi; Avan, Amir (Current Pharmaceutical Design, 2018)
Cardiovascular Disease (CVD) is one of the most important causes of morbidity and mortality, and associated with an important economic burden globally. Over the last decade, the prevalence of CVD has been rising globally, and is now associated with millions of death annually in both developed and developing countries. There is good evidence that the immune system is involved in the pathophysiology of CVD. Toll-like receptors (TLRs) and their down-stream signaling pathways play an important role in the immune system. Recent studies have suggested that the TLRs are involved in atherogenesis, including stroke, myocardial infarction, ischemiareperfusion injury, cardiac remodeling and development of Heart Failure (HF). In this review we have summarized the recent studies investigating the role of TLRs in CVD and the potential for using TLRs signaling pathways as a therapeutic target in CVD.
Keywords: Toll-like receptors